2018
DOI: 10.19113/sdufenbed.471805
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Peanut (Arachis hypogaea L.) Genotypes in Terms of Some Nutritional and Antioxidant Parameters

Abstract: The objective of this study was to investigate some nutritional and antioxidant parameters of six different peanut genotypes grown in Turkey. Unshelled seed extracts were used for analyses. The skins of the seeds were not peeled. The crude protein and the crude oil amounts, fatty acid compositions, the total phenolic and flavonoid contents and the total antioxidant capacities were investigated. The crude oil contents of seeds ranged from 43.9 to 45.9%. On the other hand, the crude protein contents varied betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Kurt, Bakal, Gulluoglu, Onat and Arıoglu (2016) found the CO content of Halisbey, Sultan, and NC-7 varieties as 46.22, 46.33, and 43.71%, respectively. Asık, Yıldız and Arıoglu (2018) found the CO contents of Sultan, NC7, Cihangir, Halisbey varieties, which were also used in our current study, as 50.40, 52.64, 49.95 and 50.77%, respectively; while Macar, Macar, Cil, Oluk and Cil (2018) stated that the CO content of different peanut varieties (Gazipasa, Sultan, NC7, Cihangir, and Halisbey) and line (DA335/2011) used in our study ranged between 43.9% and 45.9%; the difference in CO contents of the varieties were statistically insignificant; the CO contents of Gazipasa, Sultan, DA35/2011, NC-7, Cihangir, and Halisbey varieties and line were 45.0, 43.9, 44.7, 46.4, 45.5 and 45.9%, respectively; and that NC-7 variety had the highest CO content. Karabulut and Tuncturk (2019) found that the CO content of NC-7, Gazipasa, Halisbey, Sultan, and Cihangir varieties were 33.6, 35.7, 36.1, 37.4 and 36.4%, respectively.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Kurt, Bakal, Gulluoglu, Onat and Arıoglu (2016) found the CO content of Halisbey, Sultan, and NC-7 varieties as 46.22, 46.33, and 43.71%, respectively. Asık, Yıldız and Arıoglu (2018) found the CO contents of Sultan, NC7, Cihangir, Halisbey varieties, which were also used in our current study, as 50.40, 52.64, 49.95 and 50.77%, respectively; while Macar, Macar, Cil, Oluk and Cil (2018) stated that the CO content of different peanut varieties (Gazipasa, Sultan, NC7, Cihangir, and Halisbey) and line (DA335/2011) used in our study ranged between 43.9% and 45.9%; the difference in CO contents of the varieties were statistically insignificant; the CO contents of Gazipasa, Sultan, DA35/2011, NC-7, Cihangir, and Halisbey varieties and line were 45.0, 43.9, 44.7, 46.4, 45.5 and 45.9%, respectively; and that NC-7 variety had the highest CO content. Karabulut and Tuncturk (2019) found that the CO content of NC-7, Gazipasa, Halisbey, Sultan, and Cihangir varieties were 33.6, 35.7, 36.1, 37.4 and 36.4%, respectively.…”
Section: Resultssupporting
confidence: 55%
“…Arıoglu, Bakal, Gulluoglu, Kurt and Onat (2016) found that the CO contents of different peanut seed varieties [Halisbey, Sultan, NC-7, Osmaniye 2005, Batem 5025, Florispan, Brantley, Wilson, Georgia Green, Ha-runner, Flower 22 (V-1), Flower 32 (V-2), and Flower 36 (V-3)] were within the range of 47-51% and their CP contents were within the range of 24-28%. In their study determining the CP contents of Gazipasa, Sultan, DA35/2011, and NC-7; Macar, Macar, Cil, Oluk and Cil (2018) reported that Cihangir and Halisbey varieties and line, NC-7 variety had the highest CP content (30.6%), followed by the DA35/2011 line with 29.6%. There was no statistically significant difference between the CP levels of Sultan (26.9%) and Cihangir (27.2%) varieties, and the same occurred for Gazipaşa (27.7%) and Halisbey (27.8%) varieties.…”
Section: Introductionmentioning
confidence: 99%